Over-the-counter sales of antimicrobials and factors associated with it among private pharmacies in ward-32 of Kathmandu Metropolitan City: a pilot study - Koirala, Prakriti; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: Over-the-counter sales of antimicrobials are contributing to the increasing burden of anti-microbial resistance. This mixed-method study aims to assess the practice of over-the-counter sales of antimicrobials by private pharmacies and factors associated with it from the perspective of both the private pharmacy staff and the community people to produce more enriched and valid findings through triangulation of results from quantitative and qualitative studies.Method: A cross-sectional, concurrent triangulation mixed method approach was used. Participants were selected purposively, including 30 exit interviews from 5 pharmacies and 6 qualitative interviews. Descriptive statistics and Fisher’s exact test were done for quantitative analysis. Braun and Clarke’s six steps of thematic analysis were followed for qualitative data analysis.Result: Qualitative findings illuminated the repercussions of antibiotic misuse, stressing the imperative need for patient education, responsible prescribing, and regulatory measures. Identified factors included self-medication practices, familial influence, profit-driven pharmacies, easy access, healthcare system challenges, prescription barriers, and unregulated OTC sales. Quantitative results validated these, with 53.3% obtaining antibiotics without prescriptions. Key factors contributing to this trend included profit-motivated pharmacies (p=0.014), self-medication (p=0.014), the presence of a doctor in the pharmacy (p=0.005), and fear of losing customers (p=0.046).Conclusion: The integrated findings underscore urgent need to address antimicrobial misuse to curtail unnecessary expenses, adverse health effects, and the looming threat of antibiotic resistance. Comprehensive interventions are crucial to mitigate unwarranted costs, health risks, and the emergence of antimicrobial resistance, emphasizing the significance of a multifaceted approach in safeguarding global public health.